Revision Versus Primary Arthroscopic Rotator Cuff Repair: A 2-Year Analysis of Outcomes in 360 Patients. (March 2015) - Shamsudin, Aminudin; Lam, Patrick H.; Peters, Karin; Rubenis, Imants; Hackett, Lisa; Murrell, George A.C.
Background: Symptomatic rotator cuff tears are often treated surgically. However, there is a paucity of information regarding the outcomes of revision arthroscopic rotator cuff repairs. Purpose: To evaluate the outcome of revision arthroscopic rotator cuff surgery when compared with primary arthroscopic rotator cuff surgery in a large cohort of patients. Study Design: Cohort study; Level of evidence, 3. Method: A consecutive series of 50 revision arthroscopic rotator cuff repairs performed by a single surgeon, with minimum 2-year follow-up, were retrospectively reviewed using prospectively collected data. As a comparison, 3 primary arthroscopic rotator cuff repair cases (primary group; n = 310) were chosen immediately before each revision case, and 3 were chosen after. Standardized patient-ranked outcomes, examiner-determined assessments, and ultrasound-determined rotator cuff integrity were assessed preoperatively at 6 months and at a minimum of 2 years after surgery. Results: The revision group was older (mean age, 63 years; range, 43-80 years) compared with the primary group (mean age, 60 years; range, 18-88 years) ( P < .05) and had larger tear size (mean ± SEM) (4.1 ± 0.5 cm 2 ) compared with the primary group (3.0 ± 0.2 cm 2 ) ( P < .05). Two years after surgery, the primary group reported less pain at rest ( P < .02), during sleep ( P < .05), and with overhead activity ( P < .01) compared with the revision group. The primary group had better passive forward flexion (+13°; P < .05), abduction (+18°; P < .01), internal rotation (+2 vertebral levels; P < .001) and also significantly greater supraspinatus strength (+15 N; P < .001), lift-off strength (+9.3 N; P < .05), and adduction strength (+20 N; P < .01) compared with the revision group at 2 years. When compared with the primary group, the revision group was more satisfied with the overall shoulder function before surgery but was less satisfied with their shoulder function than the primary group at 2 years ( P < .005). The retear rate for primary rotator cuff repair was 16% at 6 months and 21% at 2 years, while the retear rate for revision rotator cuff repair was 28% at 6 months and deteriorated to 40% at 2 years ( P < .05). Conclusion: The short-term clinical outcomes of patients undergoing revision rotator cuff repair were similar to those after primary rotator cuff repair. However, these results did not persist, and by 2 years patients who had revision rotator cuff repair were twice as likely to have retorn compared with those undergoing primary repair. The increase in retear rate in the revision group at 2 years was associated with increased pain, impaired overhead function, less passive motion, weaker strength, and less overall satisfaction with shoulder function.